Favelizaç\~ao no Brasil entre 2000 e 2010: Resultados de uma classificaç\~ao comparável - Lucas Ferreira Mation; Vanessa Gapriotti Nadalin; Cleandro Krause (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The correct detection of the phenomena of slums is critical to the formulation of several public policies. The main sources used in Brazil are data available from population censuses, which are not comparable over time. Accordingly, the statistics office (IBGE) alerts that changes in classification procedures improved considerably the identification of slums in the 2010 Census compared to the previous census. This article presents a methodology that enables the construction of estimates of areas and populations living in slums that are comparable between 2000 and 2010. The method explores the matching of census tracts of 2000 and 2010, and then reclassifies slum areas of 2000 based on more accurate information of slum areas of 2010. Having constructed a comparable classification, we analyze the growth of population in slums and their socioeconomic indicators, both in Brazil as a whole and in the country's main metropolitan areas. The results show that while the comparison of the original data indicates that the population living in slums would have grown 75%, the corrected data show an increase of only 8,6% between 2000 and 2010. We also show that there has been a general improvement of socioeconomic indicators in slums. Generally these improvements exceeded those observed in non-slum areas.
Keywords: O18; 330; slums; subnormal agglomerations; Brazilian census